INNOVATION SYNERGY, SOCIAL CAPITAL, AND SOCIETY PARTICIPATION IN CREATING TAXPAYER COMPLIANCE IN INDONESIA - Sirri, Ahmad (universitas teuku umar, 2024)
The issue of tax compliance is significant because if taxpayers do not comply, it can lead to actions for tax avoidance, evasion and disregard will ultimately hurt the state, specifically the absence of income tax revenues from taxpayers who should comply and fulfill their duties as upstanding citizens. This research is quantitative and descriptive. Quantitative analysis uses empirical investigations that gather, examine, and present data in numerical form rather than narrative form. The population in this study is the Indonesian people, then, the sample will be determined using Purposive sampling and the requirements for working or paying taxes in Indonesia. A questionnaire served as the research instrument. which was distributed via Google form and collected 451 responses according to criteria from 573 respondents' answers. Questionnaire data processing uses a partial least squares approach. Primary data was obtained from distributing questionnaires. Reliability testing was carried out to determine the consistency of respondents' answers from time to time, as well as validity testing to determine whether the questionnaire was valid. In Indonesia, the reliability and validity of respondent response data were tested showed that all question items were declared reliable and valid. In this study, social capital and innovation have a direct effect on taxpayer compliance, and social capital and society participation have a direct relationship effect on innovation. Innovation mediates social capital and society participation.